PHYTOCHEMICAL ANALYSIS OF PORTULACA OLERACEA AND PORTULACA QUADRIFIDA EXTRACTS USING GAS CHROMATOGRAPHY–MASS SPECTROMETRY - Durgawale, Trupti P; Khanwelkar, Chitra C; Durgawale, Pratik P (Asian Journal of Pharmaceutical and Clinical Research, 2018)
Objective: The two plant species Portulaca oleracea and Portulaca quadrifida are commonly known as purslane and chickweed, respectively. They are typically consumed as salad or pickle. Traditional systems of medicine from Africa and China have described these plants belonging to family Portulacaceae as remedies against a host of diseases. Recent pharmacological investigations have revealed the importance of these plants as sources of antioxidants, essential fatty acids, and even antimicrobial agents. The objective of this study was phytochemical analysis and comparison of ethanolic extracts of these two species of Portulaca. Methods: The ethanolic extracts of both the species were prepared using Soxhlet extraction and were analyzed using gas chromatography coupled with mass spectrometry (GC–MS). Furthermore, the ethanolic extracts of fresh and dried whole plant of P. oleracea and seed of P. oleracea were studied. Results: The phytochemical constituents of ethanolic extracts of P. oleracea and P. quarifida were found to be quite different from one another and contained beneficial polyunsaturated fatty acids, alkaloids among other beneficial chemical species. Conclusion: The results of the study could be further used by researchers to assess the beneficial properties of both these species for in vitro and in vivo experiments.